Faktor Sosial dan Lingkungan yang Mempengaruhi Perilaku Masyarakat dalam Menjaga Kebersihan Lingkungan di Kecamatan Waru, Sidoarjo - Solchan Ghozali; Max Biaggie Araya Kautsar; Muhammad Yusron Maulana El-Yunusi; Didit Darmawan; Arif Rachman Putra (Nuras : Jurnal Pengabdian Kepada Masyarakat, 2026)
Environmental cleanliness is an important aspect in creating a healthy, safe, and comfortable community life. Cleanliness problems in Waru District, Sidoarjo Regency, arise due to low environmental awareness, minimal sanitation facilities, and community behavior patterns formed by social and cultural factors. The purpose of this activity is to analyze and find participatory solutions to community cleanliness problems through the Participatory Action Research (PAR) approach. The Participatory Action Research (PAR) approach emphasizes active community involvement in the process of problem identification, action planning, activity implementation, and continuous reflection of results. Data collection was carried out through observation, in-depth interviews, group discussions, and activity documentation. The results of the activity show that community participation in community service activities, community discussions, and the preparation of cleanliness programs resulted in increased environmental awareness, increased social solidarity, and the formation of a collective commitment to maintaining cleanliness. The provision of additional facilities such as waste bin arrangement, improved waste management systems, and the involvement of community leaders have a positive impact on the sustainability of the program. Based on this description, it can be concluded that the implementation of PAR is effective in building a culture of clean living because the community acts as both the subject and the primary partner in change. Active citizen involvement has been proven to strengthen environmentally conscious behavior and create sustainable cleanliness solutions.